Application of Fuzzy Mamdani Logic in Determining Teacher Performance To The Learning System at Public High School 6 Bengkulu Middle - Kms.Muhammad Apriyansah; Maryaningsih Maryaningsih; Indra Kanedi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Nowadays, the process of assessing teacher performance at State High School 6 Bengkulu Middle is still manually, namely by filling in the scores on each criterion consisting of 14 competencies, then the values are added together to get the final result of the teacher performance assessment. However, this takes quite a long time, besides that the assessment of teacher performance is only by looking at teachers who are active in various fields in the school. The application of teacher performance in State High School 6 Bengkulu Middle can help provide the results of teacher performance assessment of the learning system in schools through a fuzzy Mamdani logic approach. The application of teacher performance to the learning system at State High School 6 Bengkulu Middle was created using the Visual Basic .Net programming language and SQL Server 2008r2 Database. Based on the black box testing that has been carried out, it was found that the functionality of the teacher performance application to the learning system at State High School 6 Bengkulu Middle went well as expected and was able to analyze teacher assessment data through the Fuzzy Mamdani Method to determine teacher performance against the learning system in schools